PENGETAHUAN DAN SIKAP LANSIA SETELAH EDUKASI TENTANG PROGRAM PROLANIS DI WILAYAH KERJA PUSKESMAS MAROS BARU KABUPATEN MAROS - Nursyidatul Maulida; Hj. Sukmawati; Nadimin Nadimin (Media Gizi Pangan, 2023)
Diabetes mellitus and hypertension are health problems that are commonly found in the elderly. One of the causes is the lack of public knowledge. The purpose of the study was to determine the effect of education on changes in the level of knowledge of the elderly in the working area of the Maros Baru Health Center, Maros Regency. The research design is Quasi Experimental with one group Pre-Post test design. The research sample was the elderly who were selected by purposive sampling as many as 10 people with the criteria that the elderly had chronic hypertension or diabetes mellitus. Data collection using interviews, body weight measured using digital stepping scales and using questionnaires. Data analysis in this study used the Paired-Samples T Test. The results of the analysis showed that there was an effect of education on changes in the level of knowledge and attitudes of the elderly (p = 0.000). In conclusion, nutrition education can increase the level of knowledge and attitude of the elderly.